How chinese students learn mathematics during the coronavirus pandemic - Tanu Wijaya, Tommy (IJERI: International Journal of Educational Research and Innovation, 2020)
The Covid-19 pandemic has become a world problem now. The pandemic has affeected a lot of core sectors including the education sector. Students are not able to go to school to study and have to do a social distancing by staying at home. What the government did so that students will still be able to study at home is by developing a long-distance learning media. In this research, we will get to know more about how students in China learn mathematics at home and their learning attitude towards the learning video. This research will use a qualitative and quantitative research method. The researchers gave out questionnaires to 408 students in Guangxi province, China. The researchers also did an interview on the parents and students to know the advantages and disadvantages of using the learning video during this covid-19 pandemic. The research result shows that there is a good student learning attidude towards the learning video. Students feel that the learning video is very interesting yet effective as they were able to understand the concept taught.